2009
DOI: 10.1097/jto.0b013e318197f302
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural Administration of Pemetrexed: A Pharmacokinetic Study in an Animal Model

Abstract: While intravenous and intrapleural administration of pemetrexed yielded similar AUC and CL, the intrapleural route yielded a significantly lower C(max). As Cmax is a determinant of pemetrexed toxicity, intrapleural administration might offer a means of widening the effective therapeutic index of the drug by improving tolerability. Future studies are needed to confirm this hypothesis in malignant pleural mesothelioma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…This route of administration might consequently increase the treatment efficacy while decreasing toxicity [17]. Several drugs have been used intrapleurally such as platinum compounds [18,19], etoposide [20], paclitaxel [21] and pemetrexed [22]. We hypothesized that, compared with the intravenous route, intrapleural administration of lipoplatin would both increase pleural tissue exposure and decrease systemic exposure to the drug.…”
Section: Introductionmentioning
confidence: 99%
“…This route of administration might consequently increase the treatment efficacy while decreasing toxicity [17]. Several drugs have been used intrapleurally such as platinum compounds [18,19], etoposide [20], paclitaxel [21] and pemetrexed [22]. We hypothesized that, compared with the intravenous route, intrapleural administration of lipoplatin would both increase pleural tissue exposure and decrease systemic exposure to the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, we are interested in assessing the potential effect of pemetrexed loaded onto our polymeric films (alone and in association with cisplatin) in this rat mesothelioma model (protocol approved by the local veterinary committee). Recently, Greiller et al performed a study on rats with the aim of evaluating the pharmacokinetics of pemetrexed administered intrapleurally compared with intravenous administration [25]. They concluded that intrapleural and intravenous routes provided similar area under the plasma concentration-time curve (AUC) and total body clearance but a significantly lower maximum plasma concentration, and therefore might improve patient tolerance to pemetrexed.…”
Section: Discussionmentioning
confidence: 95%
“…In future studies, combinations of chemotherapeutic drugs, such as cisplatin with gemcitabine or cisplatin with pemetrexed, will be analysed, as combination chemotherapy appears to have a greater benefit than single-agent therapy [8,23,25]. Finally, clinical data evidence and prospective trials to confirm these basic science results are still lacking.…”
Section: Discussionmentioning
confidence: 99%